Human Gut Microbiota Dysbiosis on Pesticides Exposure - Sagar, Neha; Nandi, Sisir (Journal of Neonatal Surgery, 2025)
The gut microbiome refers to the vast community of microorganisms—mainly bacteria, but also viruses, fungi, archaea, and protozoa—that inhabit the digestive tract, primarily the intestines. These microbes form a complex ecosystem that interacts with our body, influencing digestion, metabolism, immune function, and even aspects of mental health. Dysbiosis means the loss of balance. The gut microbiota dysbiosis happens with their loss due to creating negative environment. It happens with many reasons. One of the major causes of gut microbiota dysbiosis is exposure on pesticides used in the fields. The pesticides in agricultural practices have raised concerns about its potential health effects on humans. This study explores the intricate relationship between pesticide exposure and its detrimental impact on the gastrointestinal microbiome.